Vancomycin Plus Piperacillin–Tazobactam Versus Vancomycin Plus Cefepime and the Risk of Acute Kidney Injury in Hospitalised Adults: A Meta-Analysis - Putri Indah Permata; Deka Viotra (Sriwijaya Journal of Internal Medicine, 2026)
Background: Vancomycin combined with piperacillin–tazobactam is a common empirical regimen but may increase acute kidney injury (AKI) risk. Because vancomycin is common to most comparisons, the cleanest test of the piperacillin–tazobactam effect is a head-to-head comparison against vancomycin plus cefepime. Objective: To quantify the association between vancomycin plus piperacillin–tazobactam versus vancomycin plus cefepime and AKI in hospitalised adults. Methods: PubMed/MEDLINE, Scopus and Web of Science were searched for comparative cohort studies and randomised trials in adults reporting AKI with vancomycin plus piperacillin–tazobactam versus vancomycin plus cefepime. Risk of bias was appraised with ROBINS-I and certainty with GRADE. Odds ratios (OR) were pooled using a DerSimonian–Laird random-effects model; heterogeneity (I²), a prediction interval, leave-one-out analysis and the Egger test were computed. Results: Ten cohort studies were eligible and nine (>11,000 adults) were pooled. Piperacillin–tazobactam was associated with significantly higher odds of AKI (pooled OR 1.90, 95% CI 1.43–2.52; p<0.001; I²=81%). The prediction interval (0.77–4.69) was wide, and the result was robust to leave-one-out analysis (OR 1.71–2.06). The number needed to harm ranged from about 15 to about 8 across baseline incidences of 9% to 21%. The Egger test suggested small-study effects (p=0.04); certainty was graded low. Conclusion: In hospitalised adults, vancomycin plus piperacillin–tazobactam was associated with roughly twofold higher odds of AKI than vancomycin plus cefepime; where both regimens are appropriate, cefepime may be the safer renal companion.